Juridical Review of Transition of Rights to the Owner or Seller - Ammar Rosyadi; Mohammad Roesli; Priambodo Adi Wibowo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
Land is a gift from God Almighty, therefore land is one of the supporting factors for livelihoods that are very important for the development of a just, prosperous, and prosperous society. For the sake of the progress of the nation, the Indonesian government made regulations regarding land in Indonesia, on September 24, 1960 a regulation regarding land in Indonesia was promulgated namely the Basic Agrarian Law (UUPA) Number 5 of 1960. One of the ways to achieve legal certainty and certainty of Land Rights is by registering land. The LoGA has regulated it in Article 19 of the LoGA which was then implemented, among others, in Government Regulation No. 10/1961 on Land registration (which was later declared no longer valid and replaced by Government Regulation No. 24/1997 on Land registration. This type of research used the type of research method. qualitative, namely by using a problem approach through a statutory approach. The sources and data collection used in this study are normative. The analysis used in this research is descriptive analysis method. The purpose of this study is to determine the transition rights to the owner or seller of underage land and to find out the legal consequences of the transfer of rights to the underage owner or seller.The results of this study explain that in registering the sale and purchase of property rights that are jointly owned with minors carried out before PPAT is to require a Court Determination because minors are not capable of acting in law with reference to the Criminal Code under the age of 21 years, unless they are married even though they are still under 21 years of age. In addition, the guardian's responsibility for managing the assets of minors, where the guardian acts the same as parents for minors when exercising the guardian's power, is a form of legal protection given to the assets of minors who are under the guardian's management in the form of supervision over the management. items from minors. The suggestion given by the researcher regarding the juridical review of the transfer of rights to the owner or seller of underage land is that there should be a more competent party in handling the task of supervising the responsibilities of the guardian, considering that the needs of children are currently growing and growing. Apart from that, it is imperative that the implementation of protection for minors be further improved.